Stabilizing Skills of Elementary School Teachers to Educate Students about Basic Literacy Within the Framework of an Independent Curriculum - Kartono Kartono; Dyoty Auliya Vilda Ghasya; Rio Pranata; Asmayani Salimi; Y. Touvan Juni Samodra; Suparjan Suparjan; Hery Kresnadi; Siti Halidjah; Agung Hartoyo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Teacher skills are an absolute must to oversee the implementation of an independent curriculum in schools. Teacher skills are important to continue understanding basic literacy concepts. Basic literacy skills are the foundation of all student learning, including those for science, technology, mathematics, character education, and higher order thinking skills. This strengthening carried out directly provides assistance to teachers in schools in educating students about basic literacy. Literacy is a very important thing for students to master, especially in the 21st century. Thus, this stabilization effort provides significant results for teachers and students in implementing an independent curriculum, especially at the elementary school level.